Beyond compliance: examining the completeness and determinants of WHO surgical safety checklist - a systematic review and meta-analysis - Tesfaye Engdaw Habtie; Sefineh Fenta Feleke; Aregash Birhan Terefe; Molalign Aligaz Adisu (BMC Health Services Research)
Abstract The aim of this systematic review and meta-analysis was to assess the compliance, completeness, and key barriers to the successful initiation and implementation of checklists in surgical theaters. Methods This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure the accuracy and reliability of the included studies. The protocol was registered in PROSPERO (CRD42024589344). Results The review included 13 observational studies conducted globally, encompassing a total of 17,867 participants. The overall compliance rate with the World Health Organization Surgical Safety Checklist was 73% (95% CI: 62–85%). Compliance rates for individual components were 76% for “Sign In,” 61% for “Time Out,” and 62% for “Sign Out.” The overall completeness of checklist implementation was 51%. Factors that improve compliance rate include prior Surgical Safety Checklist exposure, training, a positive work environment, management support, and regular monitoring with feedback. Conversely, barriers such as insufficient staffing, high workloads, lack of checklist ownership, resistance to change, weak audit systems, and rapid staff turnover hinder effective implementation and compliance. Conclusion Despite the importance of Surgical Safety Checklist in improving healthcare outcomes, its overall compliance rate across healthcare settings remains suboptimal, with a notably low completeness rate. This highlights the frequent omission or inconsistent application of critical checklist components. Maximizing the checklist’s full potential requires continuous efforts, including sustained support, regular audit, and strong commitment from all stakeholders. Recommendation Policymakers, healthcare administrators, and surgical teams must work together to integrate the checklist into routine workflows, ensure continuous monitoring and support, and foster a culture of safety to improve patient outcomes.